Effectiveness of E-Service Quality, E-Trust, and E-Satisfaction Mediated by Customer Satisfaction on Repur-chase Intention in bus e-ticket in the RedBus Application (Case Study at Purabaya Bus Terminal, Surabaya) - Aris Yunan Suprapto; Evi Fitrotun Najiah; Mohammad Yaskun (Sean Institute, 2024)
This research was initiated in response to numerous grievances from regular bus who feel victim to intermediaries and were charged double the standard fare. Typically passengers would remit theri bus fares directly to the conductor upon boarding the bus. A study on redBus bus e-ticket services found that e-service quality, e-trust, e-satisfaction strongly affect customer satisfaction and repurchase intention. However, e-trust doesn’t have a significant impact on repurchase intention. Conducted through online questionnnaires via Google Formulirs, the research utilized Structural Equation Model (SEM) with Partial Least Squares (PLS) approach. The research, based on 115 purposively sampled respondents., sheds light on enhancing the online bus ticketing experience and underscores the importance of e-service quality and satisfaction in fostering customer loyalty